Contributions of Syntactic Awareness to Reading in Chinese‐speaking Adolescent Readers with and without Dyslexia. (21st January 2013) - Chung, Kevin K. H.; Ho, Connie S‐H; Chan, David W.; Tsang, Suk‐Man; Lee, Suk‐Han
<x xml:space="preserve">Abstract</x> This study investigated the relative contribution of syntactic awareness to Chinese reading among Chinese‐speaking adolescent readers with and without dyslexia. A total of 78 junior high school students in Hong Kong, 26 dyslexic adolescent readers, 26 average adolescent readers of the same age (chronological age control group) and 26 younger readers matched with the same reading level (reading‐level group) participated and were administered measures of IQ, syntactic awareness, morphological awareness, vocabulary knowledge, working memory, word reading, and reading comprehension. Results showed that dyslexic readers scored significantly lower than chronological age but similarly to reading level control groups in most measures, especially in the areas of syntactic skills. Analyses of individual data also revealed that over half of the dyslexic readers exhibited certain aspects of deficits in syntactic skills. In regression analyses, syntactic skills were the strongest predictors of ability in word reading and reading comprehension measures. This study highlights the uniquely important correlates of syntactic skills in Chinese reading acquisition and impairment. Copyright © 2013 John Wiley & Sons, Ltd.